Calcium binding to S. mutans grown in the presence or absence of sucrose - Tarcísio Jorge Leitão; Livia Maria Andaló Tenuta; Guilherme Ishi; Jaime Aparecido Cury (Sociedade Brasileira de Pesquisa Odontológica, 2012)
Sucrose is the most cariogenic dietary carbohydrate because it is a substrate for insoluble extracellular polysaccharide (IEPS) production in dental biofilms, which can proportionally decrease bacterial density and, consequently, the number of biofilm calcium (Ca) binding sites. Ca bound to bacterial cell walls can be released into the biofilm fluid during a cariogenic challenge, reducing the driving force for mineral dissolution provoked by the pH drop. Thus, we investigated the effect of an IEPS-rich extracellular matrix on bacterial Ca binding after treatment with Ca solutions. Streptococcus mutans Ingbritt 1600 was cultivated in culture broths supplemented with 1.0% sucrose or 0.5% glucose + 0.5% fructose. The IEPS concentration in bacterial pellets was determined after alkaline extraction. Bacterial pellets were treated with 1 mM or 10 mM Ca++ solutions at 37ºC for 10 to 60 min. Ca binding to bacterial pellets, determined after acid extraction using the Arsenazo III reagent, was fast and concentration dependent. Although the IEPS concentration was approximately ten times higher in bacterial pellets cultivated in sucrose as compared to its monossaccharides, bound Ca concentration after Ca treatment was similar in both conditions. These results suggest that IEPS may not influence the amount of Ca bound to reservoirs of dental biofilms.